Reliabilitas Alat Ukur: Jenis-Jenis, Cara Pengukuran, dan Faktor-Faktor yang Mempengaruhinya dalam Pembelajaran - Isrofuzain; Tarno; Ahmad Rosyid Ridho (Lembaga Yasin AlSys, 2026)
Reliability is an important characteristic that learning evaluation instruments must possess because it indicates the consistency of measurement results when an instrument is used repeatedly under relatively similar conditions. An instrument with high reliability produces stable and trustworthy data that can be used as a basis for making appropriate educational decisions. This study aimed to explain the concept of measurement instrument reliability, the types of reliability, measurement methods, and the factors that influence reliability in learning. The study employed a descriptive qualitative approach using a literature review method through the examination of various sources on educational evaluation and psychological measurement. The findings showed that reliability can be measured using several approaches, namely test–retest, parallel forms, split-half, Kuder–Richardson, Cronbach’s alpha coefficient, and inter-rater reliability. The reliability level of an instrument is influenced by instrument quality, the number of test items, students’ conditions, rater objectivity, and the test administration environment. This study confirms that systematic instrument development, the selection of an appropriate reliability estimation method, and the implementation of consistent measurement procedures are required to produce reliable evaluation data. These findings contribute to strengthening the understanding of the importance of reliability in the development of assessment instruments and support educators in obtaining accurate and accountable measurement results.